Analisis Penggunaan Material Pada Bangunan Microlibrary Warak Kayu Semarang - Misbahudin Efendy; Kridha Agishna Mukti (Journal of Engineering and Applied Technology, 2025)
In the process of constructing a building, material selection is an important aspect that must be carefully considered by architects or designers. Materials not only influence the aesthetic value of a building but also play a role in determining building quality and environmental sustainability. This study analyzes the Microlibrary Warak Kayu designed by SHAU (Suryawinata Haizelman Architecture Urbanism), located on Dr. Sutomo Street, Semarang. The purpose of this research is to identify the types of materials used in the Microlibrary Warak Kayu, both in exterior and interior elements, so that it can serve as a reference for other public building designs. The research employs a qualitative descriptive method with a phenomenological approach. Data were obtained through field observations and supported by literature studies from various sources. The results indicate that all building elements of the Microlibrary Warak Kayu use wood materials certified by the Timber Legality Verification System (SVLK), with most also certified by the Forest Stewardship Council (FSC). These materials were prefabricated by PT. Kayu Lapis Indonesia and derived from processed factory wood waste. The use of sustainable materials contributes to environmental preservation and helps reduce the carbon footprint of the construction industry.